Pelatihan Pembuatan Kerajinan Ecoprint Sebagai Pengembangan Kreativitas Anak Di Sekolah Dasar Negeri Wonomerto 1 (Satu) - Dhian Satria Yudha Kartika; Fidda Rahmawati; Viona Eka Rahmawati; Agus Tri Sapta Yudha; Alfin Nur Faizah; Ruldy Rizqi Suhendri (Institut Nalanda, 2023)
The development of creativity in children is an important aspect in the current era, and one way to develop it is by providing training on ecoprint. Ecoprint is a fabric coloring technique that involves direct contact with printing. The term ecoprint consists of the wordeco,